2018
DOI: 10.24191/mar.v17i1.711
|View full text |Cite
|
Sign up to set email alerts
|

Does Stock Market Development Affect Economic Growth? Econometric Evidence From Bangladesh

Abstract: The study aims to evaluate the causality linkage between  stock market development (SMD) and growth of the economy  in Bangladesh. Using time series data of quarterly frequency through 2000Q1-2017Q4 and employing the Johansen cointegration approach the study reveals that there  are  long-run co-integrating relationships among the variables, namely, GDP, development of the stock market, net interest spread, real effective exchange rate and financial depth. The Vector Error Correction Model (VECM) confirms the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The Dhaka Stock Exchange (DSE) started functioning in 1954 and Chittagong Stock Exchange (CSE) in 1995. The liberalization of the capital market during the early 1990s brought significant positive changes to different market indicators (Mamun, Basher, Hoque, & Ali, 2018). The market is characterized by small investors (who lack fundamental knowledge of the stock market), rumor-based trade, insufficient regulatory control, a low number of institutional investors, a weak form of efficiency, and an occasional avenue for speculative foreign investors.…”
Section: The Bangladesh Capital Market and Far Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dhaka Stock Exchange (DSE) started functioning in 1954 and Chittagong Stock Exchange (CSE) in 1995. The liberalization of the capital market during the early 1990s brought significant positive changes to different market indicators (Mamun, Basher, Hoque, & Ali, 2018). The market is characterized by small investors (who lack fundamental knowledge of the stock market), rumor-based trade, insufficient regulatory control, a low number of institutional investors, a weak form of efficiency, and an occasional avenue for speculative foreign investors.…”
Section: The Bangladesh Capital Market and Far Regulationsmentioning
confidence: 99%
“…Since many have indicated that FAR practices are one of the causes behind the 2010-11 stock market crash in Bangladesh, a briefing of the regulatory setting will be valuable (Khaled, 2011; On December 5, 2010, the bull market, as a consequence of gradual progression, turned into a bubble when the DSE General Index reached 8,918.5, which was almost 5.6 times higher than four years earlier. Similarly, the turnover increased by 61.7 times, and the market capitalization to GDP ratio reached a record high of 47% (Rahman, Hossain, & Habibullah, 2017;Mamun et al, 2018). On the next day, the bubble busted with damage, resulting in the highest one-day fall of 6.7% and a further 40% fall over the next two months.…”
Section: Figure 1: Development Of Bangladesh Capital Market and Far R...mentioning
confidence: 99%
“…Our manuscript belongs to the nascent literature (Lewellyn and Bao, 2014) that is trying to explain the ex ante factors that contribute to the creation of IPOs which measure the degree of change in total market capitalization per country. Stock market development constitutes a proxy for country financial depth, real effective exchange rates and GDP (Mamun et al, 2018). This study explores one formal and two informal cultural variables rule of law, uncertainty avoidance and masculinity in a sample of 64 countries over a 15-year period (2000-2014).…”
Section: Discussionmentioning
confidence: 99%